Electromagnetic interference shielding with absorption-dominant performance of Ti3C2TX MXene/non-woven laminated fabrics. Issue 21 (November 2021) - Zhang, Hengyu; Chen, Jianying; Ji, Hui; Wang, Ni; Feng, Shuo; Xiao, Hong
Electromagnetic interference (EMI)-shielding materials with remarkable shielding effectiveness (SE) based on dominant absorption are highly desirable, especially if they are also flexible and lightweight. Herein, we prepared MXene (Ti3 C2 TX, TX -=O, -OH, -F)-based lightweight and absorption-dominant EMI-shielding non-woven fabrics. In view of the porosity and soft properties of textiles, as well as the unique high conductivity and hydrophilicity of Ti3 C2 TX MXene, Ti3 C2 TX MXene was coated on the fiber skeleton of three different non-woven fabrics made from polyester, cotton, and calcium alginate. The conductive layer formed by Ti3 C2 TX MXene on the fiber led to heterogeneous interfaces. They improved the multiple reflection of electromagnetic waves among Ti3 C2 TX MXene sheets and then contributed to the attenuation of the electromagnetic waves. Among all the samples, calcium alginate/Ti3 C2 TX MXene reached a maximum SE of 25.26 dB at 12.4 GHz with the fabric thickness of 3.17 mm. Cotton/Ti3 C2 TX MXene achieved maximum SSEt (ratio of specific shielding effectiveness (SSE) to thickness) of 2301.95 dB cm 2 g −1 at 1.36 mm with a loading of Ti3 C2 TX MXene of only 5.77mg/cm 3 . Further, fabric thickness, layer number, conductivity, and substrate type were selected to analyze the EMI-shielding mechanism.